Documento de voluntades anticipadas: actitud de los pacientes de atención primaria - Santosde Unamuno, C (Aten Primaria, 2003)
OBJECTIVE: To find the attitude of health centre patients to the Document of Wishes stated in Advance (DWA) DESIGN: Descriptive cross-sectional study using a specially designed questionnaire SETTING: Urban health centre in Palma de Mallorca PARTICIPANTS: 132 users of a primary care clinic in Palma de Mallorca, seen between 21/6/2002 and 15/7/2002. Criteria for exclusion: <40 years old, first visit, major physical or psychological disease at time of visit and advanced neoplasia MAIN MEASUREMENTS: Patients received written information on the DWA along with the selfadministered questionnaire that consisted of five closed questions and free comment RESULTS: 107 questionnaires were received back (81%). 57.6% were women; and mean age was 55 (40–87). 97% thought the DWA was interesting. 39.3% said they would formalise a DWA and a further 39.3% thought it possible they would. If they did so, 88.8% wanted to discuss it with family members and 73.8% with their family doctor. 32.1% had already talked «clearly» with their family members about terminal care, and 31.1% had talked «in general terms». 36.8% said they had not talked about it. 86% found it «not at all uncomfortable» to read the document. 38 respondents wrote comments about a dignified death, freedom to decide, the relevance of the DWA, the importance of being informed and euthanasia CONCLUSIONS: Participants were clearly in favour of the DWA and many fully intended to formalise it. They wanted to discuss the question with family members and their doctors. Thinking about it did not make them uncomfortable. The recent legalisation of the DWA may help patients and doctors to talk openly about care at the end of life